"Mały psalm do łzy": nad "Utworami rozproszonymi" Zbigniewa Herberta = "Small psalm to tears": "The Scattered Pieces" by Zbigniew Herbert - Mikołajczak, Małgorzata (1966- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"The Scattered Pieces" by Zbigniew Herbert published in 2010 contain texts scattered in magazines,appearing out of the country and so far unpublished poems. They not only confirm the existinginterpretive clues, but also situate them in a different interpretive perspective and modify.The interpretation based on literary motives and authorial creation reveal a trend of personal,confessional and religious poetry of Herbert, showing Herbert`s dreams and longings.
Keywords: Herbert, Zbigniew (1924-1998) - twórczość; poezja polska - 20 w.; literatura polska - 20 w. - tematyka